A new therapeutic approach with tocilizumab in a 39-year-old patient with recurrent diabetic myonecrosis. Issue 1 (11th August 2021) - Wagemann, Judith; Keller, Sarah; Noriega, Maria de las Mercedes; Stenzel, Werner; Schneider, Udo; Krusche, Martin
ABSTRACT: We report the case of a 39-year-old female patient with acute painful swelling of the left thigh and symmetric muscle weakness in both upper legs. The patient had a history of long-standing, poorly controlled type 1 diabetes which required dialysis. Serum inflammatory markers were highly elevated. Magnetic resonance imaging (MRI) indicated necrotic or inflammatory colliquation. As antibiotic therapy did not lead to clinical improvement, a successful anti-inflammatory therapy with prednisolone was initiated. Three months later, the patient presented with a new onset of progressive and painful muscle swelling of the right thigh. MRI showed pronounced swelling of the right adductor muscles and inflammatory markers were massively elevated. In the absence of autoantibodies or any infectious agents and the recurrent symptomatology, relapsing diabetogenic myonecrosis was diagnosed. Initially, clinical improvement could only be achieved with high-dose glucocorticosteroids. Intravenous immunoglobulins did not show an effect, whereas serological and clinical remission was achieved after we administered tocilizumab intravenously. Diabetic myonecrosis is a rare complication of long-term, poorly controlled diabetes mellitus. Acute muscle pain and elevated inflammatory markers should prompt suspicion. Contralateral muscle involvement is also suggestive of the disease. The optimisation of diabetes treatment is crucial in order to prevent further disease complications.